Local uses and traditional knowledge of Nibung (Oncosperma tigillarium) in Riau Province, Indonesia - DESTI DESTI; RETNO MASTUTI; RODIYATI AZRIANINGSIH; ESTRI LARAS ARUMINGTYAS (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Desti D, Mastuti R, Azrianingsih R, Arumingtyas EL. 2024. Local uses and traditional knowledge of Nibung (Oncosperma tigillarium Jack. Ridl.) in Riau Province, Indonesia. Biodiversitas 25: 2043-2050. Nibung (Oncosperma tigillarium Jack. Ridl.), the symbolic plant of Riau Province, serves as its mascot flora. This research analyzes the local uses and traditional knowledge of nibung in both coastal and non-coastal areas of Riau, Indonesia. Ethnobotanical information regarding nibung was gathered from local communities through interviews, conducted with a structured questionnaire, supplemented by field observations and discussions with community members. Respondents were chosen using purposive and snowball sampling methods. It found that more than five types of utilization of nibung practiced by the local community, consisting of constructions, tools and utensils, medicinal purposes, as a source of vegetables or additional food, and for flavoring some dishes. In this case, stem is the highest part of nibung, which was used by the local people. In the coastal areas show a higher utilization of nibung compared to the non-coastal areas. Respondents show an understanding of the cultural and socio-economic importance of nibung, reflecting local wisdom in its utilization. They selectively harvest mature plants, leaving saplings to grow and thrive, only take a mature one, and leave the saplings to grow. Before cutting down nibung trees, they carefully choose the mature ones, and avoid cutting down those without shoots in a clump. In this investigation, the local wisdom regarding the cutting of nibung among Riau's coastal communities is known as the "memenyan" tradition. Before harvesting nibung, they perform the tradition of burning incense ("kemenyan") as a ritual for seeking permission to cut down the nibung. On the other hand, in the non-coastal areas, its tradition involves the datuk penghulu and ninik mamak, elders who play a crucial role in granting permission to cut nibung. It support conservation efforts through sustainable utilization and engaging local communities within the nibung's habitat.